Climate Change Totems and Discursive Hegemony Over the Arctic - Tam, Chui-Ling; Chew, Suzanne; Carvalho, Anabela; Doyle, Julie (Frontiers in Communication, 2021)
The Arctic and its animals figure prominently as icons of climate change in Western imaginaries. Persuasive storytelling centred on compelling animal icons, like the polar bear, is a powerful strategy to frame environmental challenges, mobilizing collective global efforts to resist environmental degradation and species endangerment. The power of the polar bear in Western climate imagery is in part derived from the perceived “environmental sacredness” of the animal that has gained a totem-like status. In dominant “global” discourses, this connotation often works to the detriment of Indigenous peoples, for whom animals signify complex socio-ecological relations and cultural histories. This Perspective article offers a reflexive analysis on the symbolic power of the polar bear totem and the discursive exclusion of Indigenous peoples, informed by attendance during 2015-2017 at annual global climate change negotiations and research during 2016-2018 in Canada’s Nunavut Territory. The polar bear’s totem-like status in Western imaginaries exposes three discursive tensions that infuse climate change perception, activism, representation and Indigenous citizenship. The first tension concerns the global climate crisis, and its perceived threat to ecologically significant or sacred species, contrasted with locally lived realities. The second tension concerns a perceived sacred Arctic that is global, pristine, fragile and “contemplated”, but simultaneously local, hazardous, sustaining and lived. The third tension concerns Indigenization, distorted under a global climate gaze that reimagines the role of Indigenous peoples. Current discursive hegemony over the Arctic serves to place Indigenous peoples in stasis and restricts the space for Arctic Indigenous engagement and voice.